2001
DOI: 10.1073/pnas.191388398
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of gene expression in learning by the neuronal ELAV-like mRNA-stabilizing proteins

Abstract: The view that memory is encoded by variations in the strength of synapses implies that long-term biochemical changes take place within subcellular microdomains of neurons. These changes are thought ultimately to be an effect of transcriptional regulation of specific genes. Localized changes, however, cannot be fully explained by a purely transcriptional control of gene expression. The neuron-specific ELAV-like HuB, HuC, and HuD RNA-binding proteins act posttranscriptionally by binding to adenine-and uridineric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 35 publications
(28 reference statements)
5
125
0
2
Order By: Relevance
“…For example, mRNA stabilization by ELAV-like proteins is required for learning and memory formation (Quattrone et al, 2001) and upregulation of bcl-2 expression is seen as highly significant in the treatment or prevention of a number of neurodegenerative disorders (Deigner et al, 2000).…”
Section: Are As the Targetmentioning
confidence: 99%
“…For example, mRNA stabilization by ELAV-like proteins is required for learning and memory formation (Quattrone et al, 2001) and upregulation of bcl-2 expression is seen as highly significant in the treatment or prevention of a number of neurodegenerative disorders (Deigner et al, 2000).…”
Section: Are As the Targetmentioning
confidence: 99%
“…Overexpression of GAP-43, a substrate of protein kinase C, has been found to enhance learning, 32 while downregulation of GAP-43 expression impairs learning. 34,61 The importance of decreased hippocampal expression of GAP-43 is emphasized by recent studies showing decreased phosphorylated GAP-43 in the hippocampus of adult FAE rats 62 and in adult FAE male offspring in response to contextual fear conditioning. 63 These results corroborate the potential significance of hippocampal GAP-43 in learning/memory impairment of FAE offspring, as animals expressing the constitutively phosphorylated form of GAP-43 exhibit increased learning.…”
Section: Effects Of Prenatal Alcohol Exposure On Behavior and Gene Exmentioning
confidence: 99%
“…31 The goals of the present study were to determine the effects of FAE and prenatal T4 administration on the adult offspring's spatial learning and memory and depressive behavior, and on the expression of genes known to be associated with these behaviors in specific brain regions. The selected genes, GAP-43 [32][33][34] and glucocorticoid receptor (GR), 35 have been extensively studied and implicated in learning, and GR has also been suggested to influence behavior in the FST. [36][37][38][39] Materials and methods…”
mentioning
confidence: 99%
“…In vitro analyses have shown that these proteins can bind to AREs (19, 22, 26 -31). Experiments in tissue culture, in vitro decay analyses, and in vivo studies have demonstrated direct effects of Hu proteins on the levels and/or stability of ARE-containing mRNAs (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Hu proteins have also been implicated in cancer, as they are overexpressed in neuroblastoma and small cell lung cancer, two types of cancer that show stabilization of labile proto-oncogene mRNAs such as those of the MYC, MYCN, and FOS genes (35,46,47).…”
mentioning
confidence: 99%